Um estudo sobre a produtividade total dos fatores em setores de diferentes intensidades tecnólogicas - Souza, José Antonio de (2009)
The basic hypothesis and core of this dissertation is that various methods of estimating production functions produce different results when applied to sectors of different technological intensity. This dissertation focused on determining the total factor productivity in several industries. Four sectors with high technological intensity and four sectors of low technology intensity were selected for assess this hypothesis. Production functions were estimated and its residue used to calculate the productivity. The correlation between residuals and the explanatory variables inherent to this procedure, including that of simultaneity, omitted variables and selection, was taken into account. One goal of this study was to identify whether a particular method would be more suitable to estimate production functions for industries with low/high technological intensity. This work studied several methods to estimate production functions, including: Olley & Pakes, and Levinsohn & Petrin. Our results show that, for industries with low and with high technological intensity, the Olley & Pakes method estimates are marginally better than the ones from Levinsohn & Petrin. In our opinion, such results do not provide enough advantage to put away the Levinsohn & Petrin method as a method to estimate production functions. The sensitivity of results to the different methods suggests that all of them should be consulted. In addition to the previously stated results, this work identified that the sectors studied experienced a productivity decline or stagnation from 1996 to 2005.